In regard to the question of macroscopic differential diagnosis of alcoholic and dilated cardiomyopathy - O. V. Sokolova; J. A. Petrova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The differential diagnosis of alcoholic and dilated cardiomyopathy according to the macroscopic data is represented in the article. The identity of macroscopic changes of heart, related to alcoholic and dilated cardiomyopathy, cannot diagnose these diseases based on the macroscopic characteristics; especially if there are no other visceral manifestations typical for chronic alcoholism.